2016
DOI: 10.1182/blood-2016-05-714030
|View full text |Cite
|
Sign up to set email alerts
|

Integrating clinical features and genetic lesions in the risk assessment of patients with chronic myelomonocytic leukemia

Abstract: Key Points• Risk assessment is crucial in patients with CMML because survival may range from a few months to several years.• Integrating clinical features, morphology, and genetic lesions significantly improves risk stratification in CMML.Chronic myelomonocytic leukemia (CMML) is a myelodysplastic/myeloproliferative neoplasm with variable clinical course. To predict the clinical outcome, we previously developed a CMML-specific prognostic scoring system (CPSS) based on clinical parameters and cytogenetics.In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
261
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(280 citation statements)
references
References 43 publications
16
261
1
2
Order By: Relevance
“…SF3B1 and U2AF1 mutations recur in MD‐CMML variant, whilst mutations affecting the RAS pathway, RUNX1, and EZH2 are more common in the MP‐CMML variant . Of these, ASXL1 mutations are of particular importance as they have been correlated with adverse prognosis and a poor overall survival . Such mutational profile may have clinical repercussions in the near future, as target molecules targeting the RAS signaling pathway and the spicing machinery are under investigation …”
Section: Diagnostic Workup Of Suspected Cases Of Cmmlmentioning
confidence: 99%
“…SF3B1 and U2AF1 mutations recur in MD‐CMML variant, whilst mutations affecting the RAS pathway, RUNX1, and EZH2 are more common in the MP‐CMML variant . Of these, ASXL1 mutations are of particular importance as they have been correlated with adverse prognosis and a poor overall survival . Such mutational profile may have clinical repercussions in the near future, as target molecules targeting the RAS signaling pathway and the spicing machinery are under investigation …”
Section: Diagnostic Workup Of Suspected Cases Of Cmmlmentioning
confidence: 99%
“…4,6,24 A recent study identified RUNX1, NRAS, and SETBP1 as additional somatic gene mutations with prognostic relevance. 30 Combinations of mutations appear to have specificity for monocytosis and are highly enriched in CMML. For example, comutation of TET2 and SRSF2 was associated with monocytosis in .90% of cases in on series.…”
Section: The (Lack Of) Genomic Heterogeneity In Cmmlmentioning
confidence: 99%
“…If ASXL1 RUNX1 and SETBP1 mutations appear detrimental in most series [3,15,[55][56][57], the prognosis of TET2, SRSF2 and RAS/CBL mutations seems more controversial, perhaps because of interactions with other gene mutation status [58], clinical variables such as myeloproliferative features, or with treatment. Finally, rare mutations such as those in EZH2 or DNMT3A are probably of poor prognosis [59,60], but only very large series will allow to incorporate them into molecular stratifications.…”
Section: Prognosismentioning
confidence: 99%
“…The GFM score can thus be used in centers relying on Sanger sequencing. Recently, the CPSS was integrated with molecular data to derive CPSS-mol that accounts for the poor prognosis of ASXL1, RUNX1, NRAS and SETBP1 mutations, and thus requires access to NGS for practicality [57]. Two other scores integrating clinical and molecular features, one from the Mayo clinic and the other from an international consortium have also been proposed [62,63].…”
Section: Prognosismentioning
confidence: 99%